Management Style and Productivity in Two Cultures - Morris, Tom; Pavett, Cynthia M. (Journal of International Business Studies, 1992)
Global competition has motivated an increasing number of United States firms to set up production facilities in Mexico. This study examines productivity and management style differences in a Mexican maquiladora operation and its U.S. parent plant Likert's System 4 Theory was used as the theoretical basis of comparison. As hypothesized, significant differences were found in the management systems while productivity at the two facilities was equal.